CONTEXTUAL ACCEPTANCE OF PHYSICAL VIOLENCE AGAINST WIVES: SURVEY AMONG INDONESIAN SOCIAL WELFARE COLLEGE STUDENTS - Rusyidi, Binahayati; Yuningsih, Yuyun; Zulhaeni, Zulhaeni; Loho, Albertina N.; Rahakbaw, Nancy; Humaedi, Sahadi (Share : Social Work Journal, 2020)
ABSTRACT Social workers have high potential to deal with issues and victims of violence against women through their professional services. Therefore, it is important for future social workers to be well prepared with the appropriate attitudes about the issues. This study investigated factors associated with contextual acceptance of physical violence against wives that was derived from feminist, social learning and socio-demographics perspectives.  Respondents were recruited non-randomly using convenience sampling technique. Respondents were 438 male and female undergraduate students with the average age of 20 years old. Participants were recruited from 2 private and 2 public universities located in the province of West Java, Yogyakarta, Maluku and Papua. The study found that students who knew well the victim of wife abuse, studied at universities in Western Indonesia, acknowledged themselves as Muslims, reported higher level of religiosity and endorsed egalitarian attitudes toward gender roles tended to report non-justification of wife beating. Findings were discussed within the framework of social work education strategy to improve social work students’ attitudes toward violence against wives.